KEEFEKTIFAN DISKUSI CROSSES-OVER GROUP UNTUK MENINGKATKAN KREATIVITAS SISWA - Nugroho, Ananda Prasetyo Dwi; Wiyanti, Sri; Abdet, Chadidjah Husain (Consilium: Jurnal Program Studi Bimbingan dan Konseling, 2017)
The objective of this research was to examine the effectivity of crosses-over group discussion to increase vocational students? creativity. Crosses- over group discussion was a discussion technique that every member of the group switching in certain period until there would be only one person left in the group. Quasi Eksperimental Design was used in this research. The students with low creativity level as the subject of the research. The subjects were divided into two groups, 25 students as experimental group and 25 students as control group. The instrument used in this research was creativity quisioner for doing pretest and posttest. The researcher used Mann-Whitney technique and clinical analysis to analyze the data. The result of Mann-Whitney test was 24.500 with 0,05 as the significance number (0,000<0,05). It showed that there were different scores between experimental group subject and control group subject after the subjects were given crosses-over group discussion as the treatment. The result proved crosses-group discussion increased the creativity of students at vocational school effectively.